Satuan Gaya Bahasa dan Gaya Bahasa Alegori dalam Geguritan Kori Karya Krishna Miharja - Safarina, Reny Anindhita; Sulanjari, Bambang; Werdiningsih, Yuli Kurniati (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of writing this paper is to fulfil lecture assignments and to describe allegorical language style and units of style in the geguritan entitled Kori by Krishna Miharja. As a poet, Krishna Miharja not only writes geguritan, but also short stories (cerkak). Although he wrote a lot of geguritan, Krishna is better known among Javanese writers as a witty writer. Because of the cerkak Krishna's works, which tend to be surrealistic and contain social and political criticism, they are considered as other colours in Javanese literature. The method used in this research is the content analysis method. The research data is in the form of Kori's geguritan text which tells the number of choices that must be chosen in life by being expressed using an allegorical language style. The theory used is a stylistic study which explains the style of language used in literature to reveal the message or meaning conveyed by the author in his literary work. The result of this research is that there is a story about the way of life that must be chosen among the many choices of life paths that exist. Life has many choices and humans are only trying to get the best and worthy choice for their lives.